2017
DOI: 10.2217/nnm-2016-0315
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Cisplatin to Tumor Xenografts Via the Nanoparticle Component of nano-diamino-tetrac

Abstract: NDAT markedly enhances cisplatin delivery to urinary bladder cancer xenografts and increases drug efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
6
33
0
2
Order By: Relevance
“…13 The goal of the delivery system is to achieve increased anticancer drug content within tumors and to reduce systemic toxicity. Evidence presented in this article and in a companion article on cisplatin delivery 23 validates this concept. We show here that the loading with paclitaxel or doxorubicin of the PLGA nanoparticle covalently linked to NDAT resulted in a 5-fold increase in the tumor content of paclitaxel and a 2.3-fold increase in tumor doxorubicin compared to conventional drug administration.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…13 The goal of the delivery system is to achieve increased anticancer drug content within tumors and to reduce systemic toxicity. Evidence presented in this article and in a companion article on cisplatin delivery 23 validates this concept. We show here that the loading with paclitaxel or doxorubicin of the PLGA nanoparticle covalently linked to NDAT resulted in a 5-fold increase in the tumor content of paclitaxel and a 2.3-fold increase in tumor doxorubicin compared to conventional drug administration.…”
Section: Discussionsupporting
confidence: 57%
“…In the companion article in which the tumor delivery of cisplatin by NDAT was studied, we also found a 5-fold enhancement of tumor content of drug, compared to conventionally administered cisplatin. 23 The multifold increase in the tumor content of each of these widely used anticancer drugs supports the existence of the cancer-targeting property of NDAT. 31,32 NDAT (Nanotetrac), alone, is an anticancer agent, but the dose of NDAT (0.3 mg/kg daily) used in the current studies to deliver generic chemotherapeutic agents was suboptimal in terms of NDAT chemotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, data demonstrated that treatment with anti-angiogenic drugs results in a more efficient normalized vasculature that might allow for improved tumor delivery of drugs [63,64,65,66,67,68,69,70]. Additionally, other anti-angiogenesis strategies such as anti-αvβ3 integrin have been exploited for enhanced active targeted delivery into tumors [71,72]. …”
Section: Side Effects In Anti-angiogenic Therapymentioning
confidence: 99%
“…Tetraiodothyroacetic acid (tetrac) is a deaminated analog of T 4 that competes with thyroid hormone for a target or receptor on cell surface integrin α v β 3 and blocks the activity of thyroid hormone at this site . In addition to blocking the binding of thyroid hormone to integrin α v β 3 , tetrac and its nanoparticulate derivative nano‐diamino‐tetrac inhibit cancer cell proliferation and angiogenesis by disordering the expression of a number of genes relevant to apoptosis and blood vessel formation.…”
Section: The Interactions Between Steroid Hormones and Resveratrolmentioning
confidence: 99%